(untitled) (The Agriculturists, 2017)
An experiment was carried out to study the density dependent growth of silver barb (Barbonymus gonionotus) for a period of 2 months during14 March to 18 May, 2013 in ponds with individual water area of 2.0 decimal. The experiment was conducted with three treatments, replicated three times, where stocking densities were 50, 100 and 150 fish/decimal in T1, T2 and T3, respectively. Feeds were supplied twice daily throughout the study period. Sampling was done at weekly interval throughout the experimental period. Water quality parameters were monitored weekly. Temperature ranged from 26.40 to 30.13°C, transparency from 32.36 to 46.23 cm, dissolved oxygen from 4.80 to 5.83 mg/l and pH from 6.68 to 8.11. During the study period, growth parameters were analyzed. The mean weight gains were 52.48, 49.98 and 47.87 g, the percent weight gains were 2560.16, 2438.37 and 2335.12, the average daily weight gains were 0.82, 0.78 and 0.74 g, the specific growth rates were 5.12, 5.05 and 4.98%, the survival rates were 89.6, 86.67 and 82.11% in T1, T2, and T3, respectively. There were significant differences among T1, T2 and T3 for all the growth parameters. The total productions of silver barb were 603.85, 1114.00 and 1518.06 kg/ha/2 months in T1, T2 and T3, respectively. The present study indicates that the growth of silver barb was density dependent when grown in monoculture systems and the best stocking density for production was 150 fish/decimal. The Agriculturists 2016; 14(2) 61-66